Aspek Ontologi Ilmu Pengetahuan - Syafriadi, Amri; Mulia, Trisnaldi; Ulan Sari Pardi, Putri; Pardi, Nofriyanti; Ardimen (Indo-MathEdu Intellectuals Journal, 2025)
An ontological understanding of science is crucial to building solid theories, relevant methodologies, and scientifically accountable concepts. As a branch of philosophy, ontology aims to explore the meaning of existence and examine the basic characteristics of everything that exists, both concrete and abstract. Islamic education aims to form character, morals, and knowledge based on comprehensive Islamic teachings. The application of ontology in Islamic education management not only helps in formulating educational goals, but also provides direction in the strategy and implementation of education that is in line with Islamic values. This study uses the literature study method to review and analyze information from various relevant literature sources, such as scientific journals, books, research reports, and academic articles related to the topic discussed. Based on the results of the research, there are three well-known ontological theories, namely: Idealism, which teaches that there is something real in the world of ideas, The real reality is not what is seen, but what is invisible. Materialism, argues that there is something that is actually material or completely dependent on the material. Ontology helps scientists in determining what is the object of study and how they understand the existence of the object